THE IDEOLOGY OF THE ISLAMIC MOVEMENT OF THE PROSPEROUS JUSTICE PARTY (A CASE STUDY OF PKS MEDAN POLONIA) - Arantika, Saufi; Wirman, Wirman; Fitriani, Fitriani (Journal Analytica Islamica, 2025)
The Prosperous Justice Party (PKS) is one of the Islamic-based political parties in Indonesia with strong ideological roots, often associated with transnational Islamic da'wah movements, especially the Muslim Brotherhood from Egypt. This study aims to analyze the Islamic movement ideology promoted by PKS in Medan Polonia. The research method used is a descriptive qualitative approach through interviews, observations, and document analysis. The findings indicate that PKS remains committed to Islamic values as its ideological foundation while exhibiting pragmatic and moderate strategies in local political contexts. PKS integrates da'wah with political and social activities through tarbiyah-based approaches, community service, and interpersonal communication. The transformation from an exclusive da'wah movement to an inclusive political party illustrates PKS's adaptability in facing the dynamics of Indonesian democracy.